(untitled) (Journal of Mathematical Study, 2021)
In this paper, we study a new two-step iteration scheme of mixed type for two total asymptotically nonexpansive self mappings and two total asymptotically nonexpansive non-self mappings and establish some weak convergence theorems in the framework of uniformly convex Banach spaces. Our results extend and generalize several results from the current existing literature.